Foundations towards the future: FutPrInt50 TLARs an open approach. Issue 1 (January 2021) - Eisenhut, D; Windels, E; Reis, R; Bergmann, D; Ilário, C; Palazzo, F; Strohmayer, A
Abstract: A hybrid-electric regional aircraft for 50 passengers has challenges in technology, operation and future regulations similar to larger class aircraft. It is thus at the right spot to drive technology, regulations and operational developments in order to accelerate cleaner flight technologies based on propulsion electrification. The FutPrInt50 team set up Top-Level Aircraft Requirements that aim to be a reference foundation for the development of specific topics handled in this H2020 project but also drive the open collaboration model adopted by FutPrInt50. In this paper the development of the mission statement will be explained for a hybrid-electric 50 passenger regional aircraft, which builds the framework for the Top-Level Aircraft Requirements. To further support development from these requirements, a mission scenario will be presented for this class of aircraft.